HOW EFFECT FINANCIAL RATIO AND COMPANY SIZE ON ISLAMIC SOCIAL REPORTING DISCLOSURE - Afandi, Muhammad Farhan; Meylianingrum, Kurniawati (I-Finance Journal, 2023)
This study aims to determine the effect of Profitability Ratio, Liquidity Ratio, Company Size on Islamic Social Reporting (ISR) disclosure at Islamic Banks registered in JII for the 2018-2022 period. The data used in this study is secondary data with documentation data collection techniques and literature studies sourced from financial statements. Sample selection using purposive sampling method. The data analysis used was panel data regression with eviews 10. The results of this study show that the variables of Profitability Ratio proportioned by ROA and Company Size portioned by Total Assets have no effect on the disclosure of Islamic Social Reporting (ISR). Meanwhile, the variable Liquidity Ratio portioned by FDR has a negative and significant effect on the disclosure of Islamic Social Reporting (ISR). Then the results of this study show that ROA, FDR, and Company Size together or simultaneously have a positive and significant effect on the disclosure of Islamic Social Reporting (ISR).